Unity of Science As A New Paradigm to Strengthen The Governance and Quality of Islamic Educational Institutions - Berliana Cahyani Putri; Syamsul Ma’arif; Fatkuroji (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The concept of Unity of Science has developed as an important paradigm in efforts to overcome the dualism of knowledge that still influences the governance and quality of Islamic educational institutions. This dualism has an impact on the fragmentation of institutional management, the learning process, and the relevance of graduate competencies. This study aims to analyze the application of the Unity of Science as an integrative paradigm in the governance and quality management of Islamic educational institutions, not limited to the curriculum aspect alone. This study uses a qualitative approach based on literature studies with descriptive analysis of sources in the form of scientific journal articles, academic books, and relevant policy documents. The research stages include a review of the theoretical basis of Unity of Knowledge, mapping of the concept of Islamic education governance, and an integrative analysis of the relevance and implementation of this paradigm in a managerial context. The results show that Unity of Knowledge can function as a conceptual framework that strengthens institutional governance through the integration of spiritual values, scientific rationality, and professional practices in education management. This research confirms the theoretical contribution of the Unity of Knowledge as a comprehensive paradigm for the governance and quality improvement of Islamic educational institutions. In conclusion, the application of the Unity of Knowledge paradigm has the potential to improve the quality of Islamic educational institution management to be more adaptive and systematic.